Emergency Medical Services (EMS) Utilization in Zimbabwe: Retrospective Review of Harare Ambulance System Reports - Monalisa Muchatuta; Soman Mudariki; Loretta Matheson; Brian Rice; Midion Chidzonga; Rebecca Walker; Matthew Strehlow; Jennifer Newberry (Ubiquity Press, 2022)
Background: Emergency medical services (EMS) are a critical but often overlooked component of essential public health care delivery in low- and middle-income countries (LMICs). Few countries in Africa have established EMS and there is scant literature to provide guidance for EMS growth. Objective: This study aimed to characterize EMS utilization in Harare, Zimbabwe in order to guide system strengthening efforts. Methods: We performed a retrospective chart review of patient care reports (PCR) generated by the City of Harare ambulance system for patients transported and/or treated in the prehospital setting over a 14-month period (February 2018 - March 2019). Findings: A total of 875 PCRs were reviewed representing approximately 8% of the calls to EMS. The majority of patients were age 15 to 49 (76%) and 61% were female patients. In general, trauma and pregnancy were the most common chief complaints, comprising 56% of all transports. More than half (51%) of transports were for inter-facility transfers (IFTs) and 52% of these IFTs were maternity-related. Transports for trauma were mostly for male patients (63%), and 75% of the trauma patients were age 15-49. EMTs assessed and documented pulse and blood pressure for 72% of patients. Conclusion: In this study, EMS cared primarily for obstetric and trauma emergencies, which mirrors the leading causes of premature death in LMICs. The predominance of requests for maternity-related IFTs emphasizes the role for EMS as an integral player in peripartum maternal health care. Targeted public health efforts and chief complaint-specific training for EMTs in these priority areas could improve quality of care and patient outcomes. Moreover, a focus on strengthening prehospital data collection and research is critical to advancing EMS development in Zimbabwe and the region through quality improvement and epidemiologic surveillance.